The cost and benefit of banking regulations and controls, Chinese style - Ju, Xiaosheng; Lo, Dic (PSL Quarterly Review, 2013)
The neoclassical approach focuses its attention on the prudence of individual banks. In its objective of achieving allocative efficiency, it seeks to prevent market failures caused by the operations of the banks. In this light, it is contended that China should further its market reforms in the direction of fostering the profit maximization cum risk minimization pursuit of individual banks. Meanwhile, the Keynesian-Schumpeterian-Minskyan approach focuses its attention on coping with systemic fragility. And systemic fragility is seen as endemic to the interaction between credit expansion and contraction, productive investment, and business profitability. In this light, even if it is indeed allocatively inefficient, Chinese finance can still have its advantages in terms of promoting productive efficiency. JEL Codes: G28, E12, E44